Can the Health Beliefs Predicts High School Students’ Behavioral Intention to Adopt Heart-Health-Prevention Behavior? - Afnan Hadi Khudair, Mohammed Baqer Habeeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): This study aimed mainly to enhance high school female students’ heart-health-preventive behaviors. Methodology: Part of the study was an experimental randomized controlled trial used to guide this study. The study was carried out at Fatima Al-Zahraa High School for females in Al-Diwaniyah City. The study included a simple random sample of 142 high school female students (72 students in each of the study and control groups). The study instrument consists of subjects’ sociodemographic characteristics. It includes the Expanded Health Belief Model Scales for Heart-Health Preventive Behaviors (Perceived Susceptibility to Develop Heart Disease Scale, Perceived Severity of Heart Disease Scale, Perceived Barriers to Adopt Heart-Health Preventive Behaviors Scale, Perceived Benefits of Adopting Heart-Health Preventive Behaviors Scale, Self-Efficacy of Adopting Heart-Health Preventive Behaviors Scale, Health Motivation for Adopting Heart-Health Preventive Behaviors Scale, Subjective Norms for Adopting Heart-Health Preventive Behaviors Scale, Cues-to-Action Related to Adopting Heart-Health Preventive Behaviors Scale, and Behavioral Intention to Adopt Heart-Health Preventive Behaviors Scale. Data were analyzed using the statistical package for social science (SPSS), version 26. The statistical measures of frequency, percent, mean, standard deviation, Repeated Measures ANCOVA, linear regression, One-way analysis of variance (ANOVA), and independent-sample t-test will be used. Results of the study: The study results displayed that the administered Expanded Health Belief Model Scales for Heart-Health Preventive Behaviors-based intervention noticeably enhanced students’ Perceived Susceptibility to Develop Heart Disease, Perceived Severity of Heart Disease, Perceived Barriers to Adopt Heart-Health Preventive Behaviors, Perceived Benefits of Adopting Heart-Health Preventive Behaviors, Self-Efficacy of Adopting Heart-Health Preventive Behaviors, Health Motivation for Adopting Heart-Health Preventive Behaviors, Subjective Norms for Adopting Heart-Health Preventive Behaviors, Cues-to-Action Related to Adopting Heart-Health Preventive Behaviors, and Behavioral Intention to Adopt Heart-Health Preventive Behaviors. Conclusion: The researcher concluded that the greater the Subjective Norms for adopting heart-health-preventive behaviors, the better the Behavioral Intention of adopting heart-health-preventive behaviors. The greater the Ques-To-Action for adopting heart-health-preventive behaviors, the better the Behavioral Intention of adopting heart-health-preventive behaviors.